HIERARKI PERATURAN PERUNDANG-UNDANGAN NEGARA REPUBLIK INDONESIA SEBAGAI SUATU SISTEM - Hasananuddin Hasan (FAKULTAS HUKUM UM PAREPARE, 2017)
The State recognizes the supremacy of the constitution above all other laws and regulations, which is evident from the modification that requires a procedure that is more severe than the law-making. The 1945 Constitution of the Republic of Indonesia has been established as the basic law in the legislation and occupies the highest place in the hierarchy of Indonesian laws and regulations. Hierarchy of Regulation no. 10 of 2004 which has been amended into Law no. 12 of 2011 include the MPR Decree and the Presidential Decree which changed the word Decision to the Regulation, this complement the hierarchical suprmasi of Indonesian law as a State of law as the mandate of the Constitution.